2020
DOI: 10.1063/5.0010506
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous low energy phonon dispersion in bulk silicon-germanium observed by inelastic x-ray scattering

Abstract: We report on an anomalous mode distinct from both optical and acoustic modes in phonon dispersion curves of bulk Si1−xGex alloy with x taking the values of 0.16, 0.32, 0.45, and 0.72. The anomalous mode at approximately 13 meV was observed directly using inelastic x-ray scattering along the Γ–X ([00q]) direction. The phonon dispersion relations of the anomalous mode indicate that there was no momentum dependence, similar to those of the longitudinal and transverse optical modes (Ge–Ge, Si–Ge, and Si–Si modes).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…The LVM peak positions for the Si 1-x Ge x sample ranged from 11.4-12.9 meV and are 12.1 meV on average. These values are comparable with that reported for single-crystalline Si 1-x Ge x , 2) indicating the Gerelated local structure proposed for the single-crystalline Si 1-x Ge x is also formed in the polycrystalline Si 1-x Ge x . In contrast to the LVM for the Si 1-x Ge x sample, the energy peak position shifted towards lower energy, namely lower frequency, in the case of Si 1-x-y Ge x Sn y .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The LVM peak positions for the Si 1-x Ge x sample ranged from 11.4-12.9 meV and are 12.1 meV on average. These values are comparable with that reported for single-crystalline Si 1-x Ge x , 2) indicating the Gerelated local structure proposed for the single-crystalline Si 1-x Ge x is also formed in the polycrystalline Si 1-x Ge x . In contrast to the LVM for the Si 1-x Ge x sample, the energy peak position shifted towards lower energy, namely lower frequency, in the case of Si 1-x-y Ge x Sn y .…”
Section: Resultssupporting
confidence: 88%
“…In Si 1-x Ge x , the LVM is produced at the Ge-Ge pairs or Ge atom clusters, which are surrounded by Si atoms. 2) On the other hand, we previously reported that the EXAFS measurement on a single-crystalline Ge-rich Si 1-x-y Ge x Sn y alloy revealed that a Sn atom locates at the second nearest neighbor of a Si atom to form a Si-Ge-Sn local structure. 22) Stochastically, this local structure hardly forms spontaneously when all atoms distribute randomly.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, it is shown that the resulting quantum ion-acoustic waves exhibit distinct dispersion relations across the BCS-BEC crossover, which provide a direct route to probe the changing scattering length, as well as the BCS and BEC states. It would deserve an experimental measurement of a phonon dispersion [89] varying continuously from BCS to BEC state.…”
Section: Appendix C: Possible Comparison Between Cold Ion and Atomic Systems Over The Bcs-bec Crossovermentioning
confidence: 99%